Internationalisation strategies of Italian district SMEs: an analysis on firm-level data - Ilaria Mariotti; Giacinto Micucci; Pasqualino Montanaro (European Regional Science Association (ERSA), 2004)
Traditionally, scholars describe Italian industrial districts (IDs) as closed manufacturing systems of SMEs embedded in local contexts, able to interact with the outside only at the two ends of the value chain and where well-identified firms were in charge of managing the relationships with final markets (Becattini, 1989; 2002; Piore and Sabel, 1984). However, at the end of the nineteen-eighties and during the nineties, even local systems of SMEs (IDs) perceived the importance of increasing their contacts with firms outside the local district area. The emerging delocalisation process carried out by Italian district SMEs highlights their abilities to globalise not only by selling products manufactured locally in international markets (export-based perspective), but also in terms of the international reorganisation of local supply chains. The purpose of the paper is twofold. First, we investigate whether the internationalization strategies by district SMEs are independent or complementary to each other. Second, we test if they are linked to the lack of low-skilled labour force. The questions will be addressed using data-sample of about 700 district firms (Bank of Italy database). The paper is organised as follows. A general introduction is followed by a discussion of the internationalisation strategies adopted by Italian SMEs. Section three focuses on the internationalisation process of the IDs and offers a review of studies on the subject. Section four presents an empirical analysis on the process as undergone by a sample of district SMEs. The results of the econometric model are described in section five and some ideas for further research are forwarded in the conclusions.
Keywords: 330